2002
DOI: 10.1111/j.1749-6632.2002.tb04798.x
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic Lesions and Mitochondria DNA Deletions in Brain Microvessels as a Central Target for the Development of Human AD and AD‐Like Pathology in Aged Transgenic Mice

Abstract: We have studied the ultrastructural features of vascular lesions and mitochondria in brain vascular wall cells from human AD brain biopsy, human short postmortem brain tissues, and yeast artificial chromosome (YAC) and C57B6/SJL transgenic positive (Tg+) mice overexpressing amyloid beta precursor protein (AbetaPP). In situ hybridization using mitochondrial DNA (mtDNA) probes for human wild type, 5 kb deleted, and mouse mtDNA was performed, along with immunocytochemistry using antibodies against amyloid precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
140
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(145 citation statements)
references
References 88 publications
4
140
1
Order By: Relevance
“…Thus, although HO-1 induction may reflect an effort to increase the generation of the antioxidant biliverdin, increased turnover of mitochondrial heme proteins with release of redox-active iron and copper (147) could actually increase rather than decrease oxidative stress (148). Such a scenario is consistent with the notion that mitochondrial abnormalities (149)(150)(151) and metal accumulations, likely acting in synergistic combination, are major producers of ROS possibly responsible for both local and global oxidative stress in AD that may underlie neuronal toxicity.…”
Section: Role Of Oxidative Stress In Adsupporting
confidence: 70%
“…Thus, although HO-1 induction may reflect an effort to increase the generation of the antioxidant biliverdin, increased turnover of mitochondrial heme proteins with release of redox-active iron and copper (147) could actually increase rather than decrease oxidative stress (148). Such a scenario is consistent with the notion that mitochondrial abnormalities (149)(150)(151) and metal accumulations, likely acting in synergistic combination, are major producers of ROS possibly responsible for both local and global oxidative stress in AD that may underlie neuronal toxicity.…”
Section: Role Of Oxidative Stress In Adsupporting
confidence: 70%
“…In situ hybridization using mitochondrial DNA (mtDNA) probes for human wild type, 5kb deleted and mouse mtDNA and immunocytochemistry using antibodies against AβPP, 8-hydroxy-2′-guanosine (8OHG) and cytochrome C oxidase subunit 1 (COX) revealed similar ultrastructural localization [45,46]. As expected, there was a higher degree of amyloid deposition in the vascular walls in AD compared to aged-matched controls [45,46] and in addition, vessels with more severe lesions showed immunopositive staining for AβPP and contained large, lipid-laden vacuoles in the cytoplasm of endothelial cells. Significantly more mitochondria abnormalities were seen in microvessels where lesions occurred [45,46].…”
Section: Vascular Oxidative Stress In Alzheimer Diseasementioning
confidence: 99%
“…For example, recent studies have demonstrated a decline in polyunsaturated fatty acids (PUFA) [19,20], increased levels of lipid peroxidation markers [19,21,22], as well as protein oxidation [23,24], DNA oxidation [25][26][27] and RNA oxidation [28][29][30][31] during AD. Additionally, the presence of oxidative stress markers such as advanced glycation end products (AGE), glycoxidative end products, e.g., N ε -carboxymethyllysine and lipid peroxidation adducts are detected in both NFT and senile plaques in AD [21][22][23][24][32][33][34][35] Interestingly, our recent finding demonstrated ultrastructural features of vascular lesions and mitochondria in brain vascular wall cells from human AD brain biopsy are also suggestive of oxidative damage [45,46]. In situ hybridization using mitochondrial DNA (mtDNA) probes for human wild type, 5kb deleted and mouse mtDNA and immunocytochemistry using antibodies against AβPP, 8-hydroxy-2′-guanosine (8OHG) and cytochrome C oxidase subunit 1 (COX) revealed similar ultrastructural localization [45,46].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The heart is supposed to be the most susceptible of all the organs to premature aging and free radical-mediated oxidative stress. In agreement with this, a large body of scientific evidence indicated that oxidative stress induced by reactive oxygen species (ROS) play pivotal role in the etiology of several chronic degenerative diseases, including cardiovascular disease (Berliner and Heinecke, 1996;Sevanian and Hochstein, 1985;Aliev et al, 2002, Nunomura et al, 2001Sayre et al 2001). Conversely, the brain and the nervous system are considered to be highly susceptible to peroxide damage than most organs and tissues due to their high content of iron, catecholamine, excitatory amino acids, polyunsaturated lipid-rich neural parenchyma, high oxygen utilization accounting for one fifth of the total system consumption, low anti-oxidative enzymes, such as catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GSHPX) (Rouach et al, 1987;Patole and Ramasara, 1988;Haliwell B,1989;Juurlink and Sweeney,1997).…”
Section: Antioxidant Agentsmentioning
confidence: 97%